ABO blood group is a risk factor for coronary artery disease in patients with poor blood pressure control - Bingyang Zhou; Naqiong Wu; Chenggang Zhu; Ying Gao; Yuanlin Guo; Ping Qing; Xiaolin Li; Yao Wang; Qian Dong; Jianjun Li (Clinical and Experimental Hypertension, 2017)
Background: Few studies had examined the role of ABO blood groups on CAD in hypertensive patients with different blood pressure (BP) controls. Methods: A total of 2708 patients with primary hypertension (HTN) were consecutively enrolled and underwent coronary angiography (CAG) due to angina-like chest pain. The severity of coronary artery stenosis was assessed by Gensini score (GS). Patients were divided into two groups due to results of CAG: HTN with CAD (n = 2185) and HTN without CAD (n = 523). Poor BP control was defined as systolic BP (SBP) ≥ mean in the study. Multivariable regression analysis was used to determine the potential impact of ABO blood groups on risk of the presence and severity of CAD. Results: Compared to HTN without CAD group, the percentage of A blood group was statistically higher and O blood group was significantly lower in HTN with CAD group. Moreover, percentage of the angiography-proven CAD was higher in A blood group than that in non-A blood group (p < 0.05). After adjusting for confounding factors, A blood group was independently associated with CAD (odds ratio (OR): 1.422; 95% confidence interval (CI): 1.017–1.987; p = 0.039) and GS (β = 0.055, p = 0.046) in patients with poor BP control. Conclusions: A blood group was an independent risk factor for the presence and severity of CAD in hypertensive patients with poor BP control.